2012
DOI: 10.1186/1752-1505-6-12
|View full text |Cite
|
Sign up to set email alerts
|

The association between armed conflict, violence and mental health: a cross sectional study comparing two populations in Cundinamarca department, Colombia

Abstract: BackgroundExposure to violence in general and to armed conflict in particular has been consistently associated with an increased prevalence of mental illness. Colombia has sustained an internal armed conflict for decades and is considered one of the most violent countries in the world. However, certain areas have been more exposed to the conflict than others.MethodsThis is a cross sectional study comparing two communities from different villages in the department of Cundinamarca, Colombia. One, Guasca, was dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0
11

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 8 publications
2
23
0
11
Order By: Relevance
“…The litany of atrocities that have precipitated displacement in Colombia includes the murder of relatives, massacres, forced disappearances, torture, kidnapping, assault, sexual abuse, and other forms of violence [1••, 2••, 12–19, 49, 51, 52, 84]. Beyond whatever harm is perpetrated, the expulsion phase is most notable for the gravity, totality, and finality of loss.…”
Section: Discussionmentioning
confidence: 99%
“…The litany of atrocities that have precipitated displacement in Colombia includes the murder of relatives, massacres, forced disappearances, torture, kidnapping, assault, sexual abuse, and other forms of violence [1••, 2••, 12–19, 49, 51, 52, 84]. Beyond whatever harm is perpetrated, the expulsion phase is most notable for the gravity, totality, and finality of loss.…”
Section: Discussionmentioning
confidence: 99%
“…Also, a study in Colombia found that populations exposed to armed conflict experienced different forms of mental illness, particularly depression, somatization disorder and alcohol abuse (16). Still, another study among women in six conflict-affected areas in the north and east of Sri Lanka found substantially higher rates of early marriage, pregnancy and home births, higher levels of maternal mortality and lower levels of contraceptive use compared to other non-conflict areas (17).…”
Section: Status Of Health Services and Outcomesmentioning
confidence: 99%
“…29 Research conducted in Colombia found comparable high rates of somatization disorder in samples drawn from the populations of communities with or without intensive exposure to armed conflict (73% vs. 61%). 30 The incidence of somatic symptoms seems to be related to Hispanics' tendency to see mind, body, and spirit as a continuum and, importantly, individuals with somatization disorder are 3 times more likely to develop PTSD. 14 Furthermore, Latinos tend to experience peri-traumatic dissociation or "altered states of consciousness" during and following traumatic exposure.…”
Section: Ptes and Ptsd In The United Statesmentioning
confidence: 99%
“…A significant association was observed between exposure to armed conflict and the prevalence of psychiatric disorders while comparing the citizens of Guasca, a Colombian "pueblo" (small town) that had been occupied by the guerrilla and the citizens of Guatavita, a nearby Colombian town where armed conflict never occurred. 30 Bell et al (2012) recently conducted a study in 4 Colombian provinces that had experienced high levels of violence related to the armed conflict.…”
Section: Exposure To Armed Conflict and Violencementioning
confidence: 99%